#WelcomeRefugees: a critical discourse analysis of the refugee resettlement initiative in Canadian news - Manar Mustafa,; Zahariah Pilus, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study focuses on the frames utilized in the depiction of Syrian refugees and social and political actors involved in the Syrian resettlement in Canadian online news media. The role of the media is vital in portraying Syrian refugees' image and affects how the Canadian public perceives them. This paper focuses on utilizing the referential and predicational strategies introduced by the Discourse-Historical Approach (DHA) in framing the Syrian refugees, Liberal government, Conservative party, Canadians, and Canada (henceforth social and political actors). This study examines a total of 31 articles selected from three of the most visited Canadian news sites, namely, the Toronto Star, the Toronto Sun, and the National Post. News articles were collected beginning from the arrival of the first group of refugees in December 2015 and ending in March 2017, which marked the first anniversary of the refugees’ arrival. The results obtained show that both liberal and conservative-leaning media utilized frames in ways that correspond with their ideological stance. In most cases, the limelight rarely focused on Syrian refugees. Instead, they were used as props to push the news source's ideological convictions and to condemn and shame the opposition. Therefore, it is understood, that the framing and portrayal of refugees in this narrow manner through discursive strategies obscures the complexity of the plight of Syrian refugees and depicts them as one-dimensional characters that audiences would either fear or pity.